Awareness of Health Insurance Benefits in the Philippines : What Do People Know and How? - Bredenkamp, Caryn; Capuno, Joseph; Kraft, Aleli; Poco, Louis; Quimbo, Stella; Tan, Carlos Antonio, Jr. (World Bank, Washington, DC, 2017)
In recent years, the Philippines has seen a rapid expansion of health insurance coverage, especially among the poor. In particular, the implementation of the 2012 Sin Tax Law, which increased tobacco and alcohol excise tax and earmarked most of the incremental revenues for PhilHealth premium subsidies for indigent households, contributed to an increase in the number of families receiving government-subsidized health insurance from 5.2 million to 15.3 million poor families and senior citizens between 2012 and 2015. This paper assesses how people who are eligible for government-subsidized (free) health insurance through Philippines Health Insurance Corporation (PhilHealth) find out about their eligibility and their benefits, and also how well people know the PhilHealth benefits.